Professional networking for undergraduate students: a scaffolded approach. Issue 2 (7th February 2021) - Badoer, Emilio; Hollings, Yvette; Chester, Andrea
ABSTRACT: Online social networking has changed how individuals communicate and associate. It facilitates building new relationships and maintenance of existing relationships. As the nature of work and career is changing, developing and maintaining relationships is essential for securing employment. Making social connections from the early stages of tertiary education is important to building and maintaining social capital. Graduate employability is an increasingly important outcome for universities and they have a key role in educating students regarding professional networking skills. The present study was designed to evaluate the development of such skills through in-class activities across a four-year programme. A pre-test-post-test design was used to compare data from 102 students on their awareness, confidence and use of LinkedIn (the largest professional networking platform). Prior to scaffolded in-class activities, students in years one and three reported little confidence and fourth-year students were the most confident using LinkedIn, although most students appreciated the importance of LinkedIn to their professional development and employment prospects. Following the in-class activities, all measures increased, up to five-fold in some year levels. Student responses to the open-ended survey questions complemented the quantitative analysis. The data suggests that embedding tasks that enhance professional networking into the curriculum can improve understanding of these platforms amongst students.